Effect of sulfasalazine on inflammation and endothelial function in patients with established coronary artery disease - Tabit, Corey E; Holbrook, Monica; Shenouda, Sherene M; Dohadwala, Mustali M; Widlansky, Michael E; Frame, Alissa A; Kim, Brian H; Duess, Mai-Ann; Kluge, Matthew A; Levit, Aaron; Keaney, John F; Vita, Joseph A; et al. (Vascular medicine (London, England), 2012)
Inflammation is critical for atherosclerosis development and may be a target for risk-reduction therapy. In experimental studies, activation of the inflammatory regulator, nuclear factor kappa B (NFlB), contributes to endothelial activation and reduced nitric oxide production. We treated patients with coronary artery disease with sulfasalazine, an inhibitor of NFκB, and placebo in a randomized, double-blind, crossover study design. Brachial artery flow-mediated dilation (FMD) and digital vascular function were measured at baseline and after each 6-week treatment period. Of the 53 patients enrolled in the crossover study, 32 (age 60 ± 10, 22% female) completed all the visits, with a high rate of study withdrawal due to gastrointestinal side effects. In a subset of 10 participants, we compared the effects of 4 days of sulfasalazine treatment (n = 5) to no treatment (n = 5) on NFκB-regulated gene expression in peripheral blood mononuclear cells. Tumor necrosis factor α-stimulated expression of CD69 and NFlB subunit p50 was significantly blunted after 4 days of sulfasalazine treatment but not after no treatment. However, FMD and digital vasodilator response did not significantly change from baseline with long-term sulfasalazine treatment. Short-term sulfasalazine inhibited NFlB activity; however, long-term treatment was poorly tolerated and did not improve endothelial function. Our findings suggest that sulfasalazine therapy is not the optimal anti-inflammatory treatment for reversing endothelial dysfunction in cardiovascular disease. Further studies are warranted to investigate the potential for NFlB inhibition to reduce cardiovascular risk.